Hydrothermal synthesis of zeolites from residual waste generated via indirect carbonation of coal fly ash - Seonmi Shin; Myoung-Jin Kim (Sustainable Environment Research, 2024)
Abstract Indirect carbonation, a technology to store CO2 and produce stable CaCO3 and MgCO3, involves elution of Ca and Mg from industrial waste and subsequent carbonation. Although substantial residual waste is generated after the elution of Ca and Mg, its recycling attributes have not been adequately scrutinized. The residual waste has lower Ca and Mg contents and higher Si and Al contents than those of the raw material (i.e., industrial waste). This study involves the hydrothermal synthesis of zeolite-P using residual waste from indirect carbonation, conducted at both 100 and 180 ℃. The properties of these zeolites are compared with those synthesized from coal fly ash (CFA). The synthesized zeolites were characterized by X-ray diffraction, field emission scanning electron microscope, thermogravimetric analyzer, and Brunauer–Emmett–Teller (BET). A high zeolite conversion efficiency was achieved through a hydrothermal reaction (up to 87%), even though Si and Al were not added to the residual waste. Additionally, the cation exchange capacity and BET specific surface area of the synthesized zeolites were high (200 cmol kg−1 and 73 m2 g−1, respectively). These findings highlight the possibility of synthesizing zeolites using the residual waste from indirect carbonation as an alternative to conventional zeolite synthesis using industrial waste such as CFA. The synthesized zeolite-P is expected to be effective in wastewater treatment, detergent manufacturing, and water softening.